2020
DOI: 10.4254/wjh.v12.i8.493
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 receptor agonists in non-alcoholic fatty liver disease: An update

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the predominant cause of chronic liver disease worldwide. NAFLD progresses in some cases to non-alcoholic steatohepatitis (NASH), which is characterized, in addition to liver fat deposition, by hepatocyte ballooning, inflammation and liver fibrosis, and in some cases may lead to hepatocellular carcinoma. NAFLD prevalence increases along with the rising incidence of type 2 diabetes mellitus (T2DM). Currently, lifestyle interventions and weight loss are used as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 64 publications
(111 reference statements)
0
22
0
Order By: Relevance
“…Liraglutide, semaglutide, and exenatide treatment all improved liver biomarkers ( 19 22 ), and liraglutide decreased histological inflammation in patients with biopsy-proven NASH ( 23 ). Some studies, however, did not demonstrate any marked improvement in liver biomarkers after liraglutide treatment, or the improvements were not sustained ( 19 21 , 23 ). Two years of treatment with semaglutide significantly reduced ALT and hs-CRP levels in patients with obesity and/or type 2 diabetes, although significance was lost after adjustment for changes in body weight ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liraglutide, semaglutide, and exenatide treatment all improved liver biomarkers ( 19 22 ), and liraglutide decreased histological inflammation in patients with biopsy-proven NASH ( 23 ). Some studies, however, did not demonstrate any marked improvement in liver biomarkers after liraglutide treatment, or the improvements were not sustained ( 19 21 , 23 ). Two years of treatment with semaglutide significantly reduced ALT and hs-CRP levels in patients with obesity and/or type 2 diabetes, although significance was lost after adjustment for changes in body weight ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with GLP-1 receptor monoagonists may also improve liver biomarkers (19). Liraglutide, semaglutide, and exenatide treatment all improved liver biomarkers (19)(20)(21)(22), and liraglutide decreased histological inflammation in patients with biopsy-proven NASH (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Glucagon-like peptide-1 (GLP-1) is an important incretin and its receptor GLP-1R is widely distributed in tissues such as liver, pancreas, brain, heart and intestine. GLP-1 can increase liver fatty acid oxidation and insulin sensitivity by binding to GLP-1R, thereby improving NAFLD ( Areti et al, 2020 ). Short-chain fatty acids (SCFA), a metabolic product of the gut microbiota , can regulate the secretion of GLP-1 ( Bayer et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when compared to dulaglutide, it shows better glucose control and weight reduction in diabetic patients. The authors of the review concluded that GLP-1RA might be a promising treatment for NAFLD patients; however, further studies are needed to confirm this correlation [ 236 ]. Teshome et al also verified the efficacy of GLP-1RA in NAFLD treatment; however, only studies using liraglutide and exenatide were included in this review paper.…”
Section: Incretin Based Therapy For Obesity-related Metabolic Disomentioning
confidence: 99%